Benin : 2019 Article IV Consultation, Fourth Review under the Extended Credit Facility Arrangement, and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Benin. (IMF Staff Country Reports; Country Report, 2019)
The economy continues to grow at a fast pace, driven by port activity and cotton production. The execution of the 2019 budget is on track to bring the fiscal deficit within the WAEMU convergence criterion of 3 percent of GDP this year. Program implementation remains very satisfactory with all end-December 2018 quantitative performance criteria (QPCs) and structural benchmarks (SBs) met.